CFD analysis of NACA4415 airfoil with γ−Reθ model considering natural transition - Islam, Mazharul; Langfeldt, Felix; Juretic, Franjo; Guerrero, Joel; Wood, David (2015)
Airfoil analysis is essential to wind turbine aerodynamics. In typical operating conditions, airfoils undergo transition from laminar to turbulent flow in the boundary layer in a manner that must be modeled accurately to predict airfoil lift and drag. There are different modes of transition (e.g. natural, by-pass, wake induced, reversed, separated flow) and modeling them is not straight-forward. Over the years, diversified predictions have been developed for the various modes. One of the popular transition models is the local correlation-based $γ-Re_θ$ model of Menter et al. \citep{Menter2004}. The model requires data correlations for the transition length and the critical Reynolds numbers.